Against the tide: Recent diversity increase enhances resource use in a coastal ecosystem. (26th January 2014) - Olli, Kalle; Ptacnik, Robert; Andersen, Tom; Trikk, Olga; Klais, Riina; Lehtinen, Sirpa; Tamminen, Timo
Abstract : Biodiversity losses in marine, terrestrial, and freshwater ecosystems have raised concerns about the maintenance of sustainable ecosystem functions and services ("biodiversity crisis"). A positive diversity—productivity relationship has previously been supported by theoretical models, and by laboratory and field experiments in a variety of ecosystems including unicellular microbial communities. Here we show an increasing biomass yield of aquatic primary producers at the ecosystem scale, paralleled by a long‐term positive biodiversity change, which contrasts with the trend of global biodiversity loss. The implied direct long‐term biodiversity effect on ecosystem functioning was an increase of phytoplankton biomass per unit limiting nutrient by a factor of 1.2 to 1.4. Changes in diversity of microorganisms may have immediate implications for essential ecosystem processes like productivity and biomass yield. Diversity‐driven enhancement of resource use in primary production can lead to increased food web yields, but they also can cause a stoichiometric mismatch between autotrophs and primary consumers. Unveiling the functional roles of planktonic biodiversity therefore has essential implications both for global change and for harvestable marine resources.